2002
DOI: 10.1093/humrep/17.8.2146
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of human embryos using ethylene glycol in controlled slow freezing

Abstract: Ethylene glycol may be a good substitute for PROH to cryopreserve human embryos using a slow-freezing protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 32 publications
3
23
0
4
Order By: Relevance
“…Ethylene Glycol has proven to be a stable cryoprotectant, with less toxicity and high permeation ability suggested that Ethylene Glycol diffuses into and leaves the embryos very rapidly due to its low molecular weight, hence embryos do not undergo osmotic shock during freezing and thawing procedures. 21,22 The embryo survival rate of 96.95% with 94.17% having excellent morphology in our study, further supports this concept. Mukaida et al (1998) reported a survival rate of 81% with EG based media.…”
Section: Discussionsupporting
confidence: 82%
“…Ethylene Glycol has proven to be a stable cryoprotectant, with less toxicity and high permeation ability suggested that Ethylene Glycol diffuses into and leaves the embryos very rapidly due to its low molecular weight, hence embryos do not undergo osmotic shock during freezing and thawing procedures. 21,22 The embryo survival rate of 96.95% with 94.17% having excellent morphology in our study, further supports this concept. Mukaida et al (1998) reported a survival rate of 81% with EG based media.…”
Section: Discussionsupporting
confidence: 82%
“…It appears that the damage to the follicles observed using this cryoprotectant was caused by a toxic effect of the EG and not to the cryopreservation process. In previous studies, EG was nontoxic to human [16] and bovine [17] and [18] embryos. Moreover, good results were observed when EG was used to cryopreserve murine ovarian tissue, with 88% of follicles remaining morphologically normal after freezing/thawing [4].…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, ethylene g l y c o l ( E G ) h as b e e n u s e d w i d e l y f o r t h e vitrification of human oocytes [10,25] and embryos [26,27,30,31,[36][37][38] due to its low molecular weight, high permeation ability and low toxicity. Moreover, it has been reported that cryoprotectant mixtures may have some advantages over solutions containing only one permeable cryoprotectant [16].…”
mentioning
confidence: 99%